ANALISIS KEBERDAYAAN KONSUMEN DI KOTA X - Pandji Anoraga (Magister Manajemen STIE Bank BPD Jateng, 2021)
Today's consumers are in an increasingly complex market and are faced with an increasing amount of information with an increasingly diverse choice of products and services. Consumers are more exposed to fraud, thus requiring more expertise and knowledge than before. Thus, the government and producers are increasingly important to empower and make the best consumers aware. Law No. 8/1999 describes Consumer Protection, the main factor that becomes consumer weakness is the low level of consumer awareness of their rights. Therefore, the Consumer Protection Law is intended to be a strong legal basis for the government and non-governmental consumer protection organizations to empower consumers through consumer guidance and education. This empowerment effort is important because it is not easy to expect awareness of business actors, whose principle is to get maximum benefits.